2010
DOI: 10.1108/02683941011048373
|View full text |Cite
|
Sign up to set email alerts
|

The multicultural workplace: interactive acculturation and intergroup relations

Abstract: Purpose -The paper's aim is to introduce the interactive acculturation model (IAM) of Bourhis et al. to predict how disconcordance in acculturation orientations between host community and immigrant workers relates to the quality of intergroup work-relations. Design/methodology/approach -The sample consisted of 141 host community (Dutch) and 41 non-western immigrant workers of a postal service company who filled out a questionnaire. Methods of analyses include analysis of variance and multiple regression. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The third theme, particularly unique to immigrants, is acculturation strategies. Dutch research (Oerlemans & Peeters, ) showed that while local employees favored the full assimilation of immigrants into the local culture, immigrant employees preferred a dual orientation of partial adaptation to the host culture and partial retention of their original culture. The more local and immigrant employees disagreed on these acculturation strategies, the more it impeded their relations in the workplace, thus setting the stage for discriminatory treatment.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The third theme, particularly unique to immigrants, is acculturation strategies. Dutch research (Oerlemans & Peeters, ) showed that while local employees favored the full assimilation of immigrants into the local culture, immigrant employees preferred a dual orientation of partial adaptation to the host culture and partial retention of their original culture. The more local and immigrant employees disagreed on these acculturation strategies, the more it impeded their relations in the workplace, thus setting the stage for discriminatory treatment.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A study in the Netherlands by Oerlemans and Peeters (2010) found that while minority (mostly first-generation) employees preferred a dual pathway of adapting to the host culture whereas maintaining their own cultural heritage (integration strategy), majority employees wanted "immigrants to completely adapt to the Dutch culture, without maintaining aspects of their heritage culture" (assimilation strategy, p. 472).…”
Section: Differences Between Three Cultural Groups Of Employeesmentioning
confidence: 99%
“…Surface-level cultural diversity encompasses variations in demographic markers such as ethnicity or nationality (Jackson, May, & Whitney, 1995;Williams & O'Reilly, 1998), whereas deep-level cultural diversity involves differences in cultural attitudes, norms, and values (Jackson, Joshi, & Erhardt, 2003). Although most research thus far has focused on examining surface-level forms of cultural diversity (Oerlemans & Peeters, 2010), a growing body of research reports significant impact of deep-level forms of cultural diversity on work outcomes (Harrison et al, 1998;Harrison, Price, Gavin, & Florey, 2002;Vodosek, 2007). A recent meta-analysis of the impact of culture shows the influence of cultural values endorsed by team members to be strongest for emotional outcomes, followed by attitudes, behaviors, and, finally, performance, which has a small effect size (Taras, Kirkman, & Steel, 2010).…”
Section: Theory Developmentmentioning
confidence: 99%